Effects of polychronicity and job embeddedness on productivity of Nigerian University lecturers - Lengmang, Joy Nzeb; Dakung, Reuel J.; Auta, Habila D. (Annals of Management and Organization Research, 2024)
Purpose: The objective of this study was to examine the effect of polychronicity on university lecturer productivity. Additionally, the mediating role of job embeddedness in the relationship between polychronicity and productivity was explored. Research Methodology: This quantitative study adopted a cross-sectional design. A questionnaire was used to collect data from 300 lecturers at the University of Joseph. Multiple regression analysis was performed to test the research hypotheses using the Analysis of Moment Structures (AMOS-v23). Results: Polychronicity and job embeddedness were significantly related to productivity. In addition, this study indicates that embeddedness is a partial mediator between polychronicity and productivity. Limitations: This study focuses only on lecturers at the university of Jos, rather than all tertiary institutions in the plateau state.  However, due to contextual factors, the findings may not apply entirely to all university lecturers in the country. Hence, the model should be tested in other contexts for its reliability and validity. The study was also limited to a time frame of measurement due to the cross-sectional survey design, since the perceptions and beliefs of lecturers could change over time; thus, a longitudinal study should be considered. Contribution: This study provides valuable insights for university management to understand employee polychronic time behavior to improve their fit to jobs and organizations, which could help improve productivity. Novelty: This study explored how job embeddedness mediates the relationship between lecturers’ polychronicity and productivity. Similarly, job embeddedness played a conduit role in sustaining consistent findings between the polychronicity and productivity of lecturers at the University of Joseph.